2020
DOI: 10.1016/j.ijid.2019.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of occult hepatitis B virus infection associated with envelope protein mutations according to anti-HBs carriage in blood donors

Abstract: Occult hepatitis B virus infection (OBI) carries a risk of hepatitis B virus (HBV) transmission and hepatocellular carcinoma. As previous studies have had a limited sample size, the characteristics of OBI with genotype B and C (OBI B and OBI C ) mutations relating to hepatitis B surface antibody (anti-HBs) elicited by vaccination or a limited host immune response to HBV have not been fully explored. Methods: In this study, the occurrence of OBI B or OBI C strains associated with envelope protein (pre-S/S) amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
2
24
2
Order By: Relevance
“…Meanwhile, other kinds of E2 mutations (E2A/V/D) were observed in 1.1–7.8% of OBI strains ( p > 0.05) ( Table 1 ). In general, E2 mutations are specific and representative OBI-related mutations were found in 21.8% ( p < 0.05) of OBI subjects and none in the control group ( Table 1 ), which is consistent with a previous study in China ( Wang J. et al, 2020 ). Functional analysis showed that nearly all of the E2 mutations could significantly decrease extracellular and intracellular HBsAg level (except E2G in genotype B with increased intracellular HBsAg level) ( p < 0.05) ( Figures 1A,B ), which could partly explain the lack of HBsAg detection that characterized the occult HBV carriage in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, other kinds of E2 mutations (E2A/V/D) were observed in 1.1–7.8% of OBI strains ( p > 0.05) ( Table 1 ). In general, E2 mutations are specific and representative OBI-related mutations were found in 21.8% ( p < 0.05) of OBI subjects and none in the control group ( Table 1 ), which is consistent with a previous study in China ( Wang J. et al, 2020 ). Functional analysis showed that nearly all of the E2 mutations could significantly decrease extracellular and intracellular HBsAg level (except E2G in genotype B with increased intracellular HBsAg level) ( p < 0.05) ( Figures 1A,B ), which could partly explain the lack of HBsAg detection that characterized the occult HBV carriage in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…Wt -wild-type, aa -amino acid. Deletions at the start of pre-S1 (causing truncated l-HBs proteins) and highlighted mutations in pre-S1 have all been associated with OBI in previous studies [38,51,52]. The mutated start codon of pre-S2 has been linked with an inability to express M-HBs [53].…”
Section: Defining and Characterising Obimentioning
confidence: 92%
“…Thirdly, in occult HBV infection (OBI), HBsAg was undetectable with the existing detection methods. However, some specific mutations in preS/S gene were found in anti-HBs positive OBI samples [102] and might be adaptive substitutions selected under immune pressure. These are risk factors for virus reactivation under anti-HBs selection and changes of serological markers in OBI patients is worthy of clinical attention.…”
Section: Clinical Significance and Monitoring Suggestionsmentioning
confidence: 95%